Is a combination of individual consultations, text message reminders and interaction with a Facebook page more effective than educational sessions for encouraging university students to increase their physical activity levels? - Alsaleh, Eman (Frontiers in Public Health, 2023)
Background Physical activity (PA) has been consistently reported as a crucial component of disease prevention and improvement of people’s health. Nevertheless, data has evidenced a decline in physical activity levels among adults in Jordan. Although previous behavioral change interventions have documented efficacy in increasing physical activity among adults, the PA levels is low among adults. A new motivational intervention that focuses on changing behavior toward performing the recommended level of physical activity is on need. Objective This two-arm single-center randomized controlled trial aimed to measure the efficacy of a multi-component behavioral intervention (including goal setting, self-monitoring, and feed-back) for increasing physical activity levels and self-efficacy for exercise and decreasing body mass index and blood pressure among students at a Jordanian University. Setting Philadelphia University in Jordan. Methods A behavioral intervention based on individualized consultations, text messages reminders and interaction with a Facebook page was compared with educational sessions in terms of efficacy for increasing physical activity levels among students at Philadelphia University. Results The intervention and control groups were comparable at baseline. At 6 months a significant increase was seen in the moderate physical activity and walking levels of the intervention group compared with the control group. The mean change (SD) in total METs of moderate physical activity and walking was 503 (325.20) METs/week in the intervention group and 6 (271.20) METs/week in the control group. The mean change (SD) in steps/day was 3,000 (1,217) steps/day in the intervention group and 876 (1120.23) steps/day in the control group. The difference between mean change of the two groups was very significant at 2,124 (−820 to −563). Self-efficacy for exercise scale significantly increased among the intervention group compared with the control group. In addition, body mass index (BMI) declined from the baseline (Mean: 28.23, SD: 4.82) to 6 months (Mean: 25.36, SD: 5.23) for the intervention group. Conclusion Behavioral intervention through multicomponent strategies, alongside the implementation of an advanced communication strategy via phone and social media, is effective for motivating adult students to increase their physical activity levels. Clinical trial registration ISRCTN54100536.